Molecular phylogeny of freshwater snails and limpets (Panpulmonata: Hygrophila). Issue 2 (11th February 2020) - Saadi, Ahmed J; Davison, Angus; Wade, Christopher M
Abstract: We have undertaken a comprehensive molecular phylogenetic analysis of the Hygrophila based on 3112 sites of the large subunit and 5.8S ribosomal RNA genes. A clear basal division between Chilinoidea and Lymnaeoidea is observed. The monophyly of Acroloxidae, Lymnaeidae and Physidae is also well established. However, Planorbidae are not supported as a monophyletic group, because the Bulinidae cluster within Planorbidae. The Amphipepleinae within Lymnaeidae and both Planorbinae and Ancylinae within Planorbidae are strongly supported as monophyletic subfamilies. However, the Aplexinae within Physidae and the Lymnaeinae within Lymnaeidae are not recovered. A new taxonomic revision of the Hygrophila is proposed based on the findings of this molecular phylogeny, and the implications for the evolution of chirality are discussed.